PENGEMBANGAN LKPD INTERAKTIF BERBANTUAN LIVEWORKSHEETS PADA MATERI WUJUD ZAT DAN PERUBAHANNYA - Prasetya, Cyndi; Maisarah, Maisarah; Tanjung, Rinta Arianti; Faradilla, Meriza (UIN AR-RANIRY, 2024)
In initial observations in class IV at SDN 3 Langsa, it was found that there were still many students who had difficulty understanding the matter and their changes material and they needed supporting digital teaching materials. Hence, this article aims to develop an interactive LKPD with the help of Live worksheets on the matter and their changes material. The development of the LKPD is carried out through four stages of the Thiagarajan or 4D model. At the define stage, reasons were found related to the need to develop interactive LKPD assisted by Live worksheets which provide learning assistance in the form of attractive visuals, experiment-based, and the use of digital technology. At the design stage, an interactive LKPD was designed with the help of Live worksheets on matter and their changes material in softcopy form. At the develop stage, validation is carried out with material experts, digital teaching materials experts and linguistic experts. In the first validation, an average score of 72.59% was obtained in the valid category and the product had to be improved according to the validator's suggestions, while the average score in the second validation was 92.42% in the very valid category so that the interactive LKPD was assisted by Live worksheets on matter and their changes material are well worth sharing. At the disseminate stage, the product is implemented and distributed in class IV of state elementary schools. This article also suggests that educators use LKPD according to the characteristics of the students and the characteristics of the subject so that effective and enjoyable learning can be carried out.